2019
DOI: 10.1002/joc.6345
|View full text |Cite
|
Sign up to set email alerts
|

The climatology of cold and heat waves in Brazil from 1961 to 2016

Abstract: Extreme temperatures have caused various damages to society around the world. In Brazil, an example of that is the impact of cold and heat waves on public health. In order to analyse the temporal and spatial variability of such events, this study applied a single criterion to identify cold and heat waves. The study collected data on the events from daily temperature records from 264 weather stations over 56 years (1961–2016). The following parameters were used to describe each event: frequency, duration, sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 64 publications
1
20
0
15
Order By: Relevance
“…On the other hand, CWs are events that sometimes occur in winter, but less often in number than HWs in summer because-according to the climate classification of the study area-summers are hot and winters are not too cold [27,28]. Data on CWs and HWs in Brazil were collected from 1961 to 2016 and a study concluded that both are more severe in the southern region of the country at any time of the year [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, CWs are events that sometimes occur in winter, but less often in number than HWs in summer because-according to the climate classification of the study area-summers are hot and winters are not too cold [27,28]. Data on CWs and HWs in Brazil were collected from 1961 to 2016 and a study concluded that both are more severe in the southern region of the country at any time of the year [29].…”
Section: Introductionmentioning
confidence: 99%
“…al. [29], this study attempts to correlate extreme weather conditions and CVD hospitalizations in southern Brazil in the period from 2012 to 2017. We aim to determine whether hospitalizations due to cardiac crises have climatic associations through seasonal peaks and extreme temperature events, such as CWs and HWs, and to show how human thermal comfort indices can vary in a timeline and influence hospitalizations, especially in the worst classes of discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Na literatura são encontrados inúmeros estudos que indicam o aumento da temperatura média global para cenários futuros (Marengo & Valverde, 2007;Artaxo, 2014;Marengo, 2014;Mitchell et al, 2016), o que favorece o aumento na frequência de ocorrência de extremos climáticos, como as OCs. No Brasil, Bitencourt et al (2016Bitencourt et al ( , 2020 mostraram que o número de casos de OC apresentaram acréscimo nas últimas cinco décadas; fato observado também para todo o cone sul da América do Sul, que atingem recordes de temperaturas mediante o cenário global (Reis et al, 2017;Jacondino et al, 2018).…”
Section: Introductionunclassified
“…O teste t indica que as médias do ID são estaticamente significativas ao nível de confiança de 5% tanto na presença como na ausência de eventos de OC. Os resultados apresentados indicam que as OCs são responsáveis por alterar o conforto térmico humano na região da FNT e podem influenciar significativamente as condições térmicas experimentadas pelas pessoas que habitam nesta região.Tabela 4 -Teste t de Student entre o ID durante eventos de OC e do ID na ausência desses eventos.Os resultados encontrados neste estudo concordam com o que foi visto emBitencourt et al (2020), onde os autores mostram um aumento das OCs em todas as regiões do Brasil. Por se tratar de uma região pouco urbanizada, normalmente não é esperado os impactos das temperaturas extremas, entretanto, neste estudo foi possível observar que esse comportamento não está restrito somente a grandes centros urbanos.…”
unclassified
“…Entretanto, na presente pesquisa optou-se por utilizar a metodologia adotada por Bitencourt et al (2019) O período exato dos registos das estações meteorológicas, as suas respetivas interseções e também o percentual de falhas para as variáveis de temperatura apresentam algumas diferenças entre os dois pontos de observação (Tabela I).…”
Section: Introductionunclassified